A Correspondence between Rigid Modules Over Path Algebras and Simple Curves on Riemann Surfaces. Issue 3 (1st September 2021) - Lee, Kyu-Hwan; Lee, Kyungyong
Abstract: We propose a conjectural correspondence between the set of rigid indecomposable modules over the path algebras of acyclic quivers and the set of certain non-self-intersecting curves on Riemann surfaces, and prove the correspondence for the two-complete rank 3 quivers.